Jenis Satwa Liar dan Pemanfaatnya Di Pasar Beriman, Kota Tomohon, Sulawesi Utara - R Sahiu; E. Pangemanan; M. T. Lasut (COCOS, 2017)
ABSTRACTÂ  The research was conducted to know the kind of wildlife, parts and the way people use it. The method used ini the research during the months of August to September 2013 were interviews directly in the field against the seller and the buyer. During the course of a study period August to September found 8 wildlife traded, consisting of five wildlife found within the research that wild boars, wild rats, phyton, and bats. 3 wildlife found through information society that anoa, black macaca, and babiroussa. From interviews it is known that wild animals are imported from Gorontalo, Kotamobagu, Makassar, Minahasa, and, Bolaang Mongondow. Of the 24 respondents there were 8 people (33.33%) who buy wild animals for consumption of 3 people (12.50%), to be used as medicine, and 13 patients (54.17%) for consumption and also used as medicine. Part wildlife utilized in the form of meat (62.50%), meat and bile (25%), blood (8.33%), and fat (4.17%).Â  Key Word: Wildlife, utilization of wildlife, etnozoologi